Strategi Sentralisasi Budaya Jawa dalam Peningkatan Kualitas Pendidikan Islam: Studi Kasus di MTs Raudhatul Muttaqien Yogyakarta - Amanulloh, Mochammad Ja’far Amri; Rochmah, Ulifah Azwarani (Saneskara: Journal of Social Studies, 2024)
This study aims to describe, implement, and explore strategies to enhance the quality of Islamic education through the centralization of Javanese culture. The findings reveal a strong integration of local Javanese culture within Islamic educational institutions, reflected in various aspects such as architecture, curriculum, and extracurricular activities. Schools incorporate traditional Javanese arts and language, enriching students' educational experiences and deepening their understanding of cultural heritage. Yogyakarta's unique governance structure, emphasizing cultural preservation under the Sultanate model, provides a conducive environment for promoting these practices. The implications of this research are significant for policymakers and educators, demonstrating that cultural integration can enhance educational quality, increase student engagement, promote inclusivity, and strengthen cultural and religious identities. The study suggests the need for culturally responsive educational policies that leverage unique cultural assets to improve educational outcomes. However, the findings are context-specific to Yogyakarta, potentially limiting generalizability to other regions with different cultural and educational dynamics. Future research should explore the application of similar cultural integration strategies in diverse educational and cultural contexts and conduct longitudinal studies to assess the long-term impact of cultural centralization on education quality and student learning outcomes.